2012
DOI: 10.1016/j.jtcvs.2011.07.067
|View full text |Cite
|
Sign up to set email alerts
|

Is there a benefit of awake thoracoscopic surgery in patients with secondary spontaneous pneumothorax?

Abstract: The ELA group had a lower incidence of postoperative respiratory complications. Awake video-assisted thoracic surgery can be performed with an acceptable overall morbidity for patients with secondary spontaneous pneumothorax.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 12 publications
3
36
0
Order By: Relevance
“…Other non-randomized studies reported significant differences in hospital stay in the settings of pleural effusion (27,40), pulmonary metastasectomy (42) and secondary PNX (36). On contrary, Wu et al (33) in their study on NIVATS lobectomy in a geriatric population failed to demonstrate any difference in hospital stay length (33).…”
Section: Hospital Staymentioning
confidence: 95%
“…Other non-randomized studies reported significant differences in hospital stay in the settings of pleural effusion (27,40), pulmonary metastasectomy (42) and secondary PNX (36). On contrary, Wu et al (33) in their study on NIVATS lobectomy in a geriatric population failed to demonstrate any difference in hospital stay length (33).…”
Section: Hospital Staymentioning
confidence: 95%
“…Published data demonstrates that non-intubated techniques offer quicker recovery times, better pain scores, lower morbidity rates and shorter hospital length of stays compared with intubated surgery (6)(7)(8)(9)(10)(11)(12)(13)(14)(15) and there may also be an attenuation of stress hormone and immunologic responses (15,20,21). Awake and minimal sedation techniques also avoid the need for general anaesthesia, thus maintaining a more physiological cardiopulmonary and neurological status and avoiding post-operative nausea and vomiting.…”
Section: Potential Advantagesmentioning
confidence: 99%
“…Initial published reports on non-intubated surgery utilised thoracic epidural anaesthesia for three-port conventional VATS performed awake or under minimal sedation (6)(7)(8)(9)(10)(11)15,32,39,40). However, for simpler procedures or single port VAT surgery, epidural anaesthesia is now not deemed necessary and intercostal nerve blocks and paravertebral block are becoming more popular with the use of targeted sedation (24,25,30,31,33,34,40).…”
Section: Other Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pompeo and the Awake Thoracic Surgery Research Group [21] have shown that an intraoperative drop in the ratio of the arterial oxygen tension to the fraction of inspired oxygen may occur both in patients with normal lung and in patients with severe obstructive pulmonary disease; in the latter, it is caused by a reduction in intrinsic positive end-expiratory pressure in the peripheral alveolar region. These findings also suggest that positioning patients in the lateral decubitus position during the procedure rather than in the supine position might be preferred to reduce the perfusion of the nondependent lung and consequently the shunt fraction [21,22]. The results reported by Grendelmeier et al [15] highlight important messages.…”
mentioning
confidence: 99%